2020
DOI: 10.1111/hex.13035
|View full text |Cite
|
Sign up to set email alerts
|

Patients, caregivers and health‐care professionals’ experience with an interdisciplinary intervention for people with multimorbidity in primary care: A qualitative study

Abstract: Background: Multimorbidity challenges the health-care system and requires innovative approaches. In 2015, a 4-month patient-centred interdisciplinary pragmatic intervention was implemented in primary care with the aim of supporting self-management for patients with multimorbidity.Objective: To explore the perceptions and experiences of health-care professionals, patients and their caregivers with a 4-month patient-centred interdisciplinary pragmatic intervention in primary care. Design:A descriptive, qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
1
12
0
1
Order By: Relevance
“…The use of an interviewer and a desirability bias may explain in part this ceiling effect. 43 Also in the demonstration project, the intervention was standardized and under the control of the research team. The pragmatic nature of the present study with the intervention delivered by the professionals from the FMGs may explain the lack of improvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of an interviewer and a desirability bias may explain in part this ceiling effect. 43 Also in the demonstration project, the intervention was standardized and under the control of the research team. The pragmatic nature of the present study with the intervention delivered by the professionals from the FMGs may explain the lack of improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Complete characteristics of the participants are described elsewhere. 43 Participants reported that the intervention led to an improvement in the patients' self-efficacy, self-management, health status, and quality of life. The improvements mainly concerned certain lifestyle habits such as diet and physical exercise.…”
Section: Qualitative Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the time, having a coordinator induces greater trust, more familiarity and less anxiety for patients, caregivers and healthcare providers, but a major challenge is keeping the same coordinator throughout the process to maintain stability. Sustaining these bonds of trust in healthcare contexts where staff turnover [63] and a lack of resources [35] are common can be even more challenging. Could the continuity of transmitted information resulting from coordination minimize the impacts of personnel changes?…”
Section: Icmo-4: Discharge Planning Coordinationmentioning
confidence: 99%
“…Diversas condições patológicas são tratadas por EMD ou EID. Há relatos de atuação em equipe na abordagem a doenças crônicas, como o AVC, foco deste estudo (Xianmei, et al, 2019;Ngangue, et al, 2020). Os atendimentos ambulatoriais organizados em unidades de AVC por EMD e EID melhoram os resultados e as vantagens obtidas são persistentes, o que os torna um princípio central dos cuidados de alta qualidade para o AVC (Hustoft et al, 2018), que possui como principais causas de readmissão, as infecções, as doenças cerebrovasculares e as cardiovasculares (Philip, 2019).…”
Section: Introductionunclassified